Human Resource Management Strategies to Enhance Information Technology Adoption in MSMEs: A Review from the Organizational Innovation Perspective - Siminto (PT. LITERASI SAINS NUSANTARA, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in a country's economy. Information technology (IT) can enhance the efficiency and competitiveness of MSMEs. However, many MSMEs still face challenges in adopting this technology. This research aims to examine human resource management (HRM) strategies to enhance IT adoption in MSMEs from an organizational innovation perspective. The research method employed is a literature review with a qualitative approach utilizing descriptive analysis. The steps taken in this research involve rigorous selection of relevant articles published between 2012-2024 on Google Scholar. The study results indicate that effective HRM is key to success in adopting information technology. This involves competency mapping, fostering an organizational culture supportive of innovation, integrating HRM development into technology adoption strategies, visionary leadership, and ongoing evaluation.